2022
DOI: 10.7759/cureus.22741
|View full text |Cite
|
Sign up to set email alerts
|

Successful Debulking of Tricuspid Valve Vegetation Using Suction Filtration and Veno-Venous Bypass

Abstract: Tricuspid valve endocarditis with recurrent septic pulmonary emboli is an indication for surgery. In this report, we present a case of right-sided infective endocarditis (RSIE) in a female patient with a history of intravenous drug use (IVDU). The patient was admitted with multiple chief complaints of fatigue, chills, fever, cough, chest pain, and shortness of breath. She was found to have a large 1.8 cm (W) x 2.4 cm (L) mobile tricuspid valve vegetation on transthoracic echocardiogram (TTE). Despite being on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…A meta-analysis by Narayanan et al [6] found that in patients who had surgical intervention at seven days or less, the odds ratio (OR) of all-cause mortality was 0.61 (95% confidence interval (CI): 0.39 to 0.96, p=0.034), and in those who had surgical intervention within 8-20 days, the OR of mortality was 0.64 (95% CI: 0.48 to 0.86, p=0.003) compared with conservative management. The European Society of Cardiology (ESC) guidelines recommend surgery for right-sided IE in patients receiving appropriate antibiotic therapy who have acute severe tricuspid regurgitation resulting in right ventricular dysfunction, recurrent pulmonary emboli requiring ventilatory support or with large (>20 mm) residual tricuspid vegetations, or involvement of left-sided structures [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Narayanan et al [6] found that in patients who had surgical intervention at seven days or less, the odds ratio (OR) of all-cause mortality was 0.61 (95% confidence interval (CI): 0.39 to 0.96, p=0.034), and in those who had surgical intervention within 8-20 days, the OR of mortality was 0.64 (95% CI: 0.48 to 0.86, p=0.003) compared with conservative management. The European Society of Cardiology (ESC) guidelines recommend surgery for right-sided IE in patients receiving appropriate antibiotic therapy who have acute severe tricuspid regurgitation resulting in right ventricular dysfunction, recurrent pulmonary emboli requiring ventilatory support or with large (>20 mm) residual tricuspid vegetations, or involvement of left-sided structures [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…We also compared other case reports that match the case presented in Table S3 [ 35 , 36 ]. At presentation to the hospital, the presented case with IE was in a critical condition affecting the valve on the left side of the heart.…”
Section: Discussionmentioning
confidence: 99%